(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Children are lovely flowers of our life’s garden. Theseflower must be properly nurtured and nourished in the manner they deserve. Theyare the hope of nation, they constitute an invaluable assets for the nation(Chand, 1988). The child rearing practices are thus those techniques,which are used by the parents or other members for rearing the children (Islam,1983). Child rearing practices are aproduct of ideas, beliefs and attitude prevalent in a community on how to bringup the children. The mother’s role in child rearing is generally consideredparamount. She is regarded as the child’s best instructor, the principal personin forming the child’s character. The infant’s relationship with his mother isone of physical contact and security through the long phases of breast feeding,being carried by her and sleeping with her (Robert, 1965). Thus the bondbetween mother and child is established in the earliest stages of child’s life(Poffenberger, 1981).